Պլոտինոս կամ «Էննեսադներ» առաջին գիրքը ընդմիջարկված «Իդիոմատիկ միջանցքներով» (ՀՀ ԳԱԱ հրատ.)
В эссе рассматриваюся проблема добра и зла в философии Полтина [204 г. н. э. -270 г. н.э.],его теодические [богооправдание] взгляды,какие причины присутствия зла в мире, хотя по вопросу о происхождении зла никто не дает достаточно убедительного ответа. Также в эссе подчеркивается некоторые метафизические формулировки, несомненно связенно с плотиновской иерархии. The essay deals with the problem of good and evil in the philosophy Poltina’s teodicy approach [204 AD. e. -270 Of BC.], whether what causes the presence of evil in the world, although the questions connected with the origin of evil has one fairly convincing answer: whoever tries to answer it. Also, the essay highlights some metaphysical formulations undoubtedly connected with Plotinian hierarchy.
Keywords: Գրականություն